A look at solidarity economies: decentralization and emerging regionalism in Mexico - Diaz Muñoz, Jose Guillermo (Cooperativismo & Desarrollo, 2019)
In this paper, three experiences are analyzed as empirical referents of the social and solidarity economy in Jalisco, Mexico. This is the Alternative Rural Financing System (Arfs), a network of rural credit cooperatives; Maizud, a social company producing nixtamalized dough, and Tradoc, a cooperative of tire-producing workers. A comparison of these experiences is made from the perspective of solidary economy studies and regional studies, with their contribution and limits to inclusive and sustainable territorial alternatives. The document consists of the following sections: the social and solidarity economy as an emergency; the theoretical debates about territory, region and regionalisms; the social and solidarity economy and its relationship with the region and regionalisms; the comparative analysis of the three Jalisco experiences and, finally, some conclusive reflections.
Keywords: solidarity economies; regionalisms; territorial development; comparative analysis